Reforma del sector salud en el Perú: derecho, gobernanza, cobertura universal y respuesta contra riesgos sanitarios - Velásquez, Aníbal (2016)
In 2013, Peru initiated a reform process under the premise of recognizing the nature of health as a right that must be protected by the state. This reform aimed to improve health conditions through the elimination or reduction of restrictions preventing the full exercise of this right, and the consequent approach aimed to protect both individual and public health and rights within a framework characterized by strengthened stewardship and governance, which would allow system conduction and effective responses to risks and emergencies. The reform led to an increase in population health insurance coverage from 64% to 73%, with universalization occurring through the SIS affiliation of every newborn with no other protection mechanism. Health financing increased by 75% from 2011, and the SIS budget tripled from 570 to 1,700 million soles. From 2012 to May 2016, 168 health facilities have become operational, 51 establishments are nearing completion, and 265 new projects are currently under technical file and work continuity with an implemented investment of more than 7 billion soles. Additionally, this reform led to the approval of the Ministry of Health intervention for health emergencies and strengthened the health authority of the ministry to implement responses in case of risks or service discontinuity resulting from a lack of regional or local government compliance with public health functions.